Economic liberalisation in India - Singh, Baidyanath Prasad, 1948- (New Delhi : Ashish Pub. House, 1995)
Contributed articles.
Includes bibliographical references and index.
Keywords: India -- Economic conditions -- 1947-; India -- Economic policy -- 1991-